PENGARUH PENGGUNAAN MEDIA VIDEO YOUTUBE TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPT SPF SD NEGERI LABUANG BAJI 1 KOTA MAKASSAR - Nurul Isnaeni, Dinda; Irmawanty; Nur, A. Muafiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low learning outcomes of students in the IPAS subject due to the still conventional teaching methods and the minimal use of audio-visual media. The research problems in this study are: Is there an effect of using YouTube video media on the IPAS learning outcomes of fourth-grade students at UPT SPF SD Negeri Labuang Baji 1, Makassar City? And how are the IPAS learning outcomes of fourth-grade students who are taught using YouTube video media compared to those who are not? This study aims to determine the differences and the effect of using YouTube video media on students’ learning outcomes. The method used is a quantitative approach with a quasi-experimental type involving an experimental class and a control class, using a Non-Equivalent Control Group Pretest-Posttest Design. Data collection techniques were carried out through pretests and posttests, and the data were analyzed using descriptive and inferential analysis. The results show that the mean score of the experimental class increased from 61.05 to 85.79, while the control class increased from 59.29 to 81.90. The N-gain value for the experimental class was 0.63 and for the control class was 0.55, both categorized as moderate, with the experimental class showing a higher improvement. The hypothesis testing result indicates that the significance value is less than 0.05, meaning there is a significant difference between the two groups. Therefore, it can be concluded that the use of YouTube video media has a positive and significant effect on the IPAS learning outcomes of fourth-grade students at UPT SPF SD Negeri Labuang Baji 1 Makassar.